Assessment of arterial damage in vascular Ehlers-Danlos syndrome: A retrospective multicentric cohort - Adham, Salma; Legrand, Anne; Bruno, Rosa-Maria; Billon, Clarisse; Dalens, Violaine; Boutouyrie, Pierre; Mazzella, Jean-Michaël; Gueguen, Sonia; Frank, Michael; Mirault, Tristan; Jeunemaitre, Xavier (Frontiers in Cardiovascular Medicine, 2022)
Background: Vascular Ehlers-Danlos syndrome (vEDS) is a rare inherited connective tissue disorder due to pathogenic variants in COL3A1, leading to medium-size-artery (MSA) dissection, aneurysm, rupture. Aortic lesions are rarer and less investigated. The objective was to describe the distribution of MSA and aortic lesions and the type of COL3A1 variants in a multicentric cohort of 330 adult vEDS patients. Methods: At the time of the study, 87% were alive, 60.3% index cases, 60.0% females. COL3A1 variants were identified using NGS and/or Sanger sequencing and classified according to functional consequences: 80.6% dominant-negative (DN), 19.4% leading to haplo-insufficiency (HI). Imaging was systematically performed during the initial work-up. Carotid mechanics was assessed by echotracking in a subgroup of patients. Results: Arterial lesions were reported in 82.4% of the patients (N=272): 83.5% had MSA lesions alone, 3.3% aortic lesions alone, 13.2% both. DN variants were associated with higher prevalence of arterial lesions (P 0.044), especially on supra-aortic trunks and renal arteries. Prevalence of aortic lesions in HI patients with arterial lesions was higher than in DN patients (P 0.027) but not anymore when adjusted for age (P 0.559). Carotid Young’s modulus was lower in DN patients, in association with the higher incidence of MSA lesions in this group. Conclusion: Prevalence of aortic lesions is not influenced by COL3A1 genotype when adjusted for age. DN variants vEDS patients have a higher frequency of MSA lesions especially in supra-aortic trunks associated with lower carotid stiffness. These results support optimized care and follow-up for these vulnerable patients.